IMPLEMENTATION OF GOOD GOVERNANCE PRINCIPLES IN THE MANAGEMENT OF MILKFISH AND SHRIMP POND ENTERPRISES IN THE COASTAL AREA OF GAMPONG LAMNGA, ACEH BESAR REGENCY: PENERAPAN PRINSIP GOOD GOVERNANCE DALAM PENGELOLAAN USAHA TAMBAK BANDENG DAN UDANG DI WILAYAH PESISIRGAMPONG LAMNGA KABUPATEN ACEH BESAR - Badruzzaman; Novi Mailidarni; Akhyar; Zamzami; Tasliati Djafar; Nyak Yusfa Afrina (PT. ROCE WISDOM ACEH, 2026)
This Community Service Program (CSP) aimed to implement the principles of good governance in the management of milkfish and shrimp pond enterprises in the coastal area of Gampong Lamnga, Aceh Besar Regency. The main problems faced by the community include weak governance, limited community participation in decision-making, and the suboptimal role of village government in managing and supervising pond-based fisheries enterprises. The CSP activities were carried out through socialization sessions, focus group discussions (FGDs), institutional assistance, and evaluation of the implementation of good governance principles, including transparency, participation, accountability, and effectiveness. The results indicate improved community understanding of good governance practices, increased involvement of pond farmer groups in planning and management, and a strengthened role for village authorities as facilitators and local regulators. The implementation of good governance principles improved the management of milkfish and shrimp pond enterprises and supported sustainable coastal economic development in Gampong Lamnga.